(untitled) (Proceedings of the Global Public Health Conference, 2019)
The challenge of developing effective communication skills for public health professionals is a core requisite of inter-professional education. The World Health Organisation (2010) offered a Framework for action in inter-professional education (IPE) and inter-professional practice (IPP) which promoted ongoing collaborative practice as a key strategy to enhance patient outcomes in order to develop a practice-ready health workforce. This initiative has seen significant developments in practitioner training since this call for action. The implications of this theme impact public health and social care delivery in multi-disciplinary & multi-agency arenas, with vital service outcomes impacted by the quality of teamwork and communication. This conceptual paper focuses more closely on the crucial components of practitioner communication, with consideration of the value of empathic resonance as a core practitioner skill in inter-professional education and practice. The increased move towards casualisation in the public health workforce also poses a significant contemporary challenge for the profession and can often reflect evidence of communication break-down in professional practice which consequently impacts public health provisions. In previous papers, the author has identified the value of empathic resonance in specific professional practice settings. This enquiry now focuses more closely on public health delivery with consideration of the myriad of factors which can impact and potentially impair effective service delivery and introduces the INSPIRE model which aims to develop IPE in the curricula of public health courses.